The Effect of Credit Access on Climate Change Adaptation Strategies Among Dairy Farmers in East Java, Indonesia - Nugroho, Eko; Purwanti, Tina Sri; Rahman, Moh Shadiqur; Febrianto, Nanang; Winarto, Priyo Sugeng; Kamil, Nila (Jurnal Ilmu-Ilmu Peternakan, 2024)
This study investigated the critical issue of credit access and its implications for climate change adaptation among dairy farmers in East Java, Indonesia. Using survey cross-sectional data from a sample of 70 dairy farmers, this research employs a combination of probit modelling and propensity score matching (PSM) to examine the determinants of credit access and evaluate its impact on climate change adaptation. The findings indicate that credit access is positively and significantly associated with factors such as farming experience, family size, and the number of employed household members. These factors emerge as pivotal determinants shaping farmers' ability to secure credit. The analysis employing PSM further reveals a notable effect of credit access on climate change adaptation. Farmers with access to credit demonstrate a greater propensity to adopt and implement a greater number of climate change adaptation strategies. The positive association between credit access and climate change adaptation underscores the potential role of financial support in enhancing farmers' resilience to environmental challenges. This suggests that facilitating credit access for farmers could significantly contribute to promoting sustainable agricultural practices in the context of climate change. These findings have implications for policymakers, agricultural practitioners, and financial institutions. By leveraging these insights, targeted interventions can be devised to improve credit accessibility for farmers, thereby fostering effective climate change adaptation strategies within the agricultural sector.